Online social networking in adolescence: Patterns of use in six European countries and links with psychosocial functioning - Tsitsika, A.K.; Tzavela, E.C.; Janikian, M.; Ólafsson, K.; Iordache, A.; Schoenmakers, T.M.; Tzavara, C.; Richardson, C. (2014)
Purpose Online communication tools, such as social networking sites (SNS), have been comprehensively embraced by adolescents and have become a dominant daily social practice. Recognizing SNS as a key context of adolescent development, this study aimed to investigate associations between heavier SNS use, and adolescent competencies and internalizing problems. Methods Data was collected in six European countries: Greece, Spain, Poland, the Netherlands, Romania, and Iceland. Participants were 10,930 adolescents aged 14-17 years (F/M: 5,719/5,211; mean age 15.8 ±.7 years); 62.3% were aged 14-15.9 years and 37.7% were aged 16-17.9 years. Participants reported on their use of online communication tools, and their general competencies and internalizing problems (Youth Self Report). Results SNS are both ubiquitous - used by 70% of adolescents - and engaging, given that 40% of users spend 2 or more hours daily on SNS (labeled heavier SNS use). Heavier SNS use was associated with more internalizing problems, and the relation was consistently more pronounced among younger adolescents. Moreover, heavier SNS use was associated with lower academic performance and lower activities scores, especially for younger adolescents. In contrast, among older adolescents heavier SNS use was positively associated with offline social competence. Conclusions Although heavier SNS use is associated with higher social competence for older adolescents, it is also associated with increased internalizing problems and diminished competencies in academics and activities, especially for younger adolescents. Age, capturing developmental differences in social and regulatory skills, appears to moderate the effects of heavier SNS use on adolescent functioning. © 2014 Society for Adolescent Health and Medicine. All rights reserved.